Validasi Instrumen Penilaian Kinerja Karyawan Menggunakan Metode Behaviour Anchor Rating Scale di PT XYZ - Ismi Azalika Ummah; Leyla Ayu Azkiyah; Syamsul Hidayat (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The application of the Behaviorally Anchored Rating Scale (BARS) method in employee performance assessment has been shown to increase the objectivity and accuracy of evaluations in various organizations. The BARS method assesses performance based on specific behaviors related to a particular task, thereby reducing subjectivity in assessment. Recent research by Hia et al. (2024) shows that the integration of the BARS method with a web-based system can facilitate the process of assessing and reporting employee performance. In this study, the BARS method was applied to identify factors that affect employee performance, while the web-based system helped to summarize assessment data efficiently. In addition, research by Rouza and Yanto (2020) at Pasir Pengaraian University developed a web-based Employee Performance Assessment Information System (SIPENTAJA) using the BARS method. This system makes it easier for leaders to assess and report employee performance quickly and accurately. Thus, the application of the BARS method integrated with a web-based system at di PT XYZ, Indonesia, is expected to increase the objectivity of employee performance assessments,facilitate the evaluation process, and support better decision making in human resource management.